Characteristics of Sexual Partnerships Among Men With Diagnosed HIV Who Have Sex With Men, United States and Puerto Rico—2015–2019. (15th August 2020) - Dasgupta, Sharoda; Tie, Yunfeng; Bradley, Heather; Beer, Linda; Rosenberg, Eli S.; Holtgrave, David; Fagan, Jennifer; Green, Shana; Shouse, Roy L.
Abstract : Background: Understanding sexual partnerships of HIV-positive persons, particularly at the dyad level, can help in quantifying HIV transmission risk. We described sexual partnerships among HIV-positive men who have sex with men (MSM), including partnerships with a high risk for sexual HIV transmission. Setting: The Medical Monitoring Project is an annual, cross-sectional study that reports representative estimates on U.S. HIV-positive adults. Methods: During 2015–2019, we assessed sexual behaviors by interview, and viral load results from medical records. Among sexually active HIV-positive MSM (n = 4923), we described prevalence of high-risk sex, defined as: (1) not having sustained viral suppression, and (2) having condomless sex with an HIV-negative partner not known to be taking pre-exposure prophylaxis or an HIV-unknown partner. We described sexual partnerships among HIV-positive MSM (n = 13, 024 partnerships among 4923 MSM). For HIV-discordant partnerships (n = 7768), we reported the proportion involved in high-risk sex, and associations with high-risk sex using prevalence ratios with predicted marginal means, controlling for age of the HIV-positive partner ( P < 0.05). Results: More than half (66%) of sexually active HIV-positive MSM had condomless sex; 11% had high-risk sex. Blacks were more likely to have detectable viral loads, but less likely to have condomless sex, making prevalence of high-risk sex comparable between racial/ethnic groups. Dyad-level analyses among HIV-discordant partnerships indicated that prevalence of high-risk sex was higher among partnerships with HIV-positive white MSM, which was not observed using person-level data alone. Conclusions: In the context of ending the HIV epidemic, behavioral and clinical surveillance data can help monitor HIV transmission risk and target prevention efforts to reduce transmission among populations at disproportionate risk. Abstract : Supplemental Digital Content is Available in the Text.